Masjid Perjuangan 45 Medan City: History and Architecture: Masjid Perjuangan 45 di Kota Medan: Sejarah dan Arsitekturnya - Susanti Lingga; Achiriah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Masjid perjuangan 45 is one of the oldest mosques in Medan, North Sumatra. This mosque was built by a Tengku named Sultan Matsyeh in 1922 and became a refuge for fighters against invaders who came to North Sumatra. The purpose of this research is to find out the history and architecture of the 45th struggle mosque. This research uses qualitative research methods with a historical approach, this research contributes to understanding the history and role of the 45th struggle mosque in the context of local history and architecture so as to enrich insight into the cultural and religious heritage in this area. So that this mosque is maintained as one of the mosques that has a history of struggle in expelling invaders from Indonesia, especially North Sumatra and it is known that this mosque stands on land owned by Tengku Matseh, he is the Sultan of Percut. The architecture of this mosque itself refers to the modern architectural style and still respects the existing Islamic architectural values.